Changes in atrial electrophysiological and structural substrate and their relationship to histology in a long‐term chronic canine atrial fibrillation model. - Yamashita, Kennosuke; Silvernagel, Josh; Kwan, Eugene; Kamali, Roya; Ghafoori, Elyar; MacLeod, Robert; Dosdall, Derek J.; Ranjan, Ravi (Pacing & Clinical Electrophysiology, 2019)
Background: Atrial fibrillation (AF) is related to numerous electrophysiological changes; however, the extent of structural and electrophysiological remodeling with long‐term AF is not well characterized. Methods: Dogs (n = 6) were implanted with a neurostimulator in the right atrium (AF group). No implantation was done in the Control group (n = 3). Electroanatomical mapping was done prior to and following more than 6 months of AF. Magnetic resonance imaging was also done to assess structural remodeling. Animals were euthanized and tissue samples were acquired for histological analysis. Results: A significant increase was seen in the left atrial (LA) volume among all AF animals (22.25 ± 12.60 cm3 vs 34.00 ± 12.23 cm3, P = .01). Also, mean bipolar amplitude in the LA significantly decreased from 5.96 ± 2.17 mV at baseline to 3.23 ± 1.51 mV (P < .01) after chronic AF. Those significant changes occurred in each anterior, lateral, posterior, septal, and roof regions as well. Additionally, the dominant frequency (DF) in the LA increased from 7.02 ± 0.37 Hz to 10.12 ± 0.28 Hz at chronic AF (P < .01). Moreover, the percentage of fibrosis in chronic AF animals was significantly larger than that of control animals in each location (P < .01). Conclusions: Canine chronic AF is accompanied by a significant decrease in intracardiac bipolar amplitudes. These decreased electrogram amplitude values are still higher than traditional cut‐off values used for diseased myocardial tissue. Despite these "normal" bipolar amplitudes, there is a significant increase in DF and tissue fibrosis.